The effect of supplemental pig milk replacer on carbohydrate metabolism – a review - Pesti-Asbóth, Georgina; Novotni-Dankó, Gabriella; Győri, Zsolt; Stündl, László; Szarvas, Magdolna; Remenyik, Judit (Acta Agraria Debreceniensis, 2018)
The aim of this review is to examine the effect of milk supplementation on pigs’ carbohydrate metabolism. These parameters regulate the growth of piglets, the nutrient intake and the period of pre-weaning. Due to the increased litter size, the sow milk yield reaches an individual maximum. The individual maximum has not increased proportionally with the number of piglets born alive. The use of liquid milk supplementation may give the opportunity to keep these large litters. The examined hormones are insulin, insulin-like growth factor, growth hormone, growth hormone releasing hormone, ghrelin and leptin. This review seeks to find these hormones’ interactions.